MEMBANGUN IMAJINASI KREATIF SISWA SD MELALUI SASTRA LISAN: INTEGRASI PUISI DAN CERITA RAKYAT DALAM KELAS BAHASA INDONESIA - Juliati; Simamora, Khairunnida Br; Siregar, Khairunnisa Luthfi; Maulidya, Dara; Hilmi, Muhammad Hanif; zahwa, Aisyka Meutya (JURNAL KELUARGA SEHAT SEJAHTERA, 2025)
Creativity is one of the essential 21st-century skills, especially within the context of the Merdeka Curriculum, which emphasizes student-centered and interest-based learning. However, initial observations at SD Negeri 5 Kota Langsa revealed that fifth-grade students struggled to express original ideas, particularly in Indonesian language lessons. This study aims to develop students' creative imagination through the integration of poetry and folktales as forms of oral literature in Indonesian language learning. This research used a qualitative approach with the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, implemented in two cycles. The research subjects were 30 fifth-grade students at SD Negeri 5 Kota Langsa. Data collection techniques included observation, interviews, and documentation. The results showed an increase in student creativity, indicated by the rise in average scores of imagination, originality of ideas, poem structure, and diction from 2.58 to 4.15. The integration of poetry and folktales created a more engaging, contextual, and meaningful learning experience, and increased student participation. Thus, integrating oral literature into Indonesian language instruction is proven to be effective in fostering the creative imagination of elementary school students.